Effect of cold-induced stress on rat bladder tissue contractility and histomorphology - ERCAN, FERİHA; TARCAN, TUFAN (WILEY-LISS, 2007)
Aims: To investigate the effects of cold-induced stress on bladder tissue histomorphology and contractility in a rat model. Methods: Eighteen male Sprague-Dawley rats were divided into three groups: Control group (Group 1), acute cold-stress group (Group 2, kept at +4 degrees C for 8 hr), and chronic cold-stress group (Group 3, kept at +4 degrees C for 4 hr/day for 21 days). At the end of protocols, histological examination of general bladder tissue morphology and determination of mast cells was performed. Organ bath studies were conducted at basal tone where contractile responses to 120 mM potassium, electrical field stimulation (EFS), and carbachol (10(-9)-10(-4) M) were assessed. Relaxation responses to EFS, isoproterenol (10(-9)-10(-4) M), papaverine plus sodium nitroprusside (10(-4) M each) were recorded in carbachol pre-contracted strips. All data were compared by one-way ANOVA test. Results: Group 1 revealed regular bladder mucosa with intact urothelium. Groups 2 and 3 showed degeneration of urothelium with accumulation of neutrophils and significantly increased number of mast cells in both mucosa and muscularis. Mast cell counts were significantly higher in Group 3 compared to Group 2. Contractile responses to 120 mM potassium and EFS were significantly greater in the control group compared to other groups. Carbachol caused dose-dependent contractions that were significantly higher in the control group (at 10(-5), 3 x 10(-5), and 10(-4) M doses). There was no statistical difference between the groups in terms of relaxation responses. Conclusions: In vivo cold exposure induces significant bladder injury and decreased tissue contractility. Mechanistic pathways involved in the response of the urinary bladder to cold-induced stress need further investigation.
Keywords: bladder contractility; cold; rats; stress; CORTICOTROPIN-RELEASING-FACTOR; COOLING REFLEX; INTERSTITIAL CYSTITIS; URINARY-BLADDER; NERVOUS-SYSTEM; MICTURITION; RECEPTORS; MENTHOL; TRACT; CAT